Queenship and Cross-Confessional Idenitity - Amy Elizabeth Saunders; Johanna C E Strong; Melania Soler Moratón; Mercedes Llorente; Susannah Lyon-Whaley; Catherine Howey Stearn; Sarah Betts; Melita Thomas; Mindy Williams; Lily Feinstein (Royal Studies Journal)
This cluster focuses on the cross-confessional nature of European queenship, particularly the role which different confessional identities play in the education, marriage, childbirth, patronage, expressions of agency, legal context, and posthumous legacy of queens, both regnant and consort. Ranging from the education of Isabella I’s daughters to Catholic consorts in the Stuart realms to posthumous understandings of Anne Boleyn, this cluster features the work of both emerging and established scholars, all of whom seek to contribute to the field of royal studies’ engagement with queens’ religion across confessional lines, including intra-Christian relations and the interplay between the Christian, Jewish, and Muslim faiths. After a brief introduction to the conceptual framework of the cluster, eight discrete short-form articles examine different aspects of European queenship and their cross-confessional identities.